Review of evidence on antimicrobial resistance and animal agriculture in developing countries - Grace, Delia (CAB International, 2015)
This short paper aims to identify key evidence gaps in our knowledge of livestock- and fisheries-linked antimicrobial resistance in the developing world, and to document on-going or planned research initiatives on this topic by key stakeholders. The antimicrobial resistant (AMR) infections in animals that are of most potential risk to human health are likely to be zoonotic pathogens transmitted through food, especially Salmonella and Campylobacter. In addition, livestock associated methicillin resistant Staphylococcus aureus (LA MRSA) and extended spectrum beta lactamase E. coli (ESBL E. coli) are emerging problems throughout the world. In developing countries, AMR pathogens are commonly found in animals, animal food products and agro-food environments, but the lack of surveillance systems means there are no reliable national data on the level of AMR in animals and their products. While AMR pathogens in animals and their products undoubtedly contribute to AMR infections in people, the literature from developing countries is insufficient to draw firm conclusions on the extent of this contribution. The key driver of agriculture-related AMR is the quantity and quality of use of antimicrobials in livestock production and aquaculture. We don't have accurate information on antibiotic use in developing countries but agricultural use probably exceeds medical use; most use is probably in intensive production systems; and, use is probably increasing rapidly. The underlying driver for antimicrobial use and development of AMR is the livestock and aquaculture revolutions, by which is meant the rapid growth in intensive production systems in response to increased demand for livestock and fish products. This demand in turn is driven by population increases, urbanisation, improving economic conditions and globalisation in developing countries and is predicted to continue to increase. Based on livestock intensification patterns, China, Brazil and India are current hotspots, and future hotspots are Myanmar, Indonesia, Nigeria, Peru and Vietnam. Based on aquaculture trends, China is a hotspot and Indonesia, Thailand, Vietnam, Bangladesh, India and Chile are other countries where antimicrobial use in fish production may be problematic. Many interventions using educational, managerial, regulatory and economic approaches to improve drug use have been studied. Training by itself is relatively ineffective but if combined with strategies to change market conditions (by changing incentives and accountability environment) better success has been achieved. There are many animal husbandry options that can allow production without non-therapeutic antimicrobials, but these options have not been widely used in, or adapted to, developing countries. In developing countries, there is a dearth of evidence on most aspects of agricultural related AMR. This includes: the use of antimicrobials in agriculture; the impacts of this use on human and animal health; the acceptability and feasibility of stricter control of antibiotic use in agriculture; and, the costs and benefits of stricter control taking into account trades offs between overuse and lack of access to antimicrobial drugs. At the same time, AMR is intrinsically a global problem that can only be managed at supra-national scale and the current strong momentum to take action on AMR provides an opportunity to address the problem globally and comprehensively, addressing both medical and veterinary use. This should be done in an evidence-based way which includes filling knowledge gaps, careful piloting of interventions, and rigorous evaluation of successes and failures.